Pengaruh Kinerja Environmental, Social, and Governance terhadap Corporate Financial Performance dengan Financial Slack Sebagai Pemoderasi (Lembaga Pengembangan Kinerja Dosen, 2025)
Environmental, Social, and Governance (ESG) performance is seen as a key factor in creating long-term corporate value and influencing investor perceptions of sustainability. Meanwhile, financial slack serves as a reserve that offers flexibility to support sustainability strategies. This study aims to examine the effect of ESG performance on corporate financial performance (CFP), with financial slack acting as a moderating variable. The research focuses on energy and basic materials companies listed on the Indonesia Stock Exchange during the 2019–2023 period. The sample consists of 18 companies with 83 total observations, selected using purposive sampling. ESG data were obtained from Bloomberg. Data analysis was conducted using multiple linear regression and moderated regression analysis (MRA). The results show that ESG has a significant positive effect on CFP, while financial slack does not significantly moderate the relationship. These findings indicate that financial reserves have not been used strategically to support sustainability initiatives. ESG practices in Indonesia tend to be symbolic or merely window dressing and have yet to be fully integrated into long-term and substantive corporate strategies.